Prevalencia de sobrepeso, obesidad y dislipidemias en los alumnos de la Universidad Peruana Unión en el período comprendido de marzo a junio del 2010 - Padilla Castro, Rosa (2019)
Methodology: This descriptive study is a simple type of probabilistic stratified random sampling. An anthropometricassessment was performed in each student who participated in the study using BMI (Body Mass Index) and IndexWaist-Hip Ratio, a biochemical evaluation was also performed using indicators such as total cholesterol, HDL andLDL. In the sample who participated in this study there were 21 students in the School of Engineering, 18 studentsfrom the School of Human Sciences, 15 students from the School of Health Sciences, 16 students from the School ofTheology and finally the School of Business with 20 students. Results: In the Schools of Theology and Business Studies there is a 50% of obesity and in the School of Engineering 31.2% were overweight. On the other hand, the Schoolof Business and Theology has 50% of android type obesity (apple type) and in the School of Engineering it was founda 28.2% rate of ginecoide obesity (pear type). In the biochemical evaluation it was found that in the School of Businessthere is 35% of students with a high cholesterol level and in the School of Health Sciences there is a 33.3% of studentswho are at risk to have high cholesterol. The School of Business has 40% of students with a level of HDL. Finally, theDepartment of Human Science and Education has 33.3% of students with a high LDL level. A correlation was foundbetween the levels of waist-hip index and LDL levels with a p <-0310, which was significant compared to the BodyMass Index (BMI) which found no such correlation. Conclusions: This research shows that there exists a positivecorrelation between waist-hip ratio and LDL levels with a 0.03 significance level therefore it was found that the waisthip ratio is the best anthropometric indicator to measure the degree of obesity that a person has and thus can preventcardiovascular diseases in the future, as well as biochemical indices of LDL. It is for this reason that we recommend theuse of waist-hip ratio in adults and young people. On the other hand, the prevalence of overweight and obesity amongstudents according to each of the Schools has increased considerably compared to other years, as a hypothesis test forindependent samples we observed that there is a relationship between waist-hip ratios by gender.